Fighting for water in South Africa: public participation, water rights claiming and strengthening governance. Issue 1 (24th February 2022) - Masiangoako, Thato; Khunou, Kelebogile; Potter, Alana
Abstract: Communities in South Africa employ a diverse range of strategies to actively claim their right to water. This paper examines two rights claiming strategies – protest and litigation – through the lens of two case studies. The first case study examines the struggles of the residents of Makhanda, a small town in the predominantly rural Eastern Cape Province, who formed a coalition to advocate for the dissolution of the municipal council for failing to fulfil its constitutional mandate to provide basic services. The second case examines the struggles of the residents of Marikana, an informal settlement in the City of Cape Town, where residents are forced to live in unlit, unhygienic and undignified conditions as a result of inadequate services provision. Although access to water is a justiciable right in South Africa, there is a curious paucity of legal rights mobilisation, with only one court case reaching the Constitutional Court. The article presents the following findings. First, communities employ different methods to claim their water rights, including engagement with government through formal channels, mobilisation, protest, litigation and self-supply. Water is a justiciable human right. Second, litigation is a valuable component of rights-claiming but is most effective if used alongside other strategies like community organisation and protest. Third, water rights can be achieved alongside struggles to secure other rights, like the right to housing, or holding local government accountable. In the two case studies, the legal tools of land expropriation and provincial intervention were employed to indirectly gain access to water services. Finally, community mobilisation, combined with strategic partnerships, plays a critical role in sustaining long-term efforts to claim water rights. HIGHLIGHTS: Communities employ different methods to claim water rights including engagement with government through formal channels, community mobilisation, protest, litigation and self-supply. Litigation is a vital component of rights-claiming but is most effective used alongside other strategies like protest and community mobilisation.